Peculiarities of Antibody Genesis in the Laboratory Animals Immunized with Anthrax Protective Antigen Preparation, Bacillus anthracis Recombinant or Bacillus anthracis Vaccine Strains - P. Yu. Popova; N. I. Mikshis; A. Yu. Goncharova; T. N. Kashtanova; Yu. A. Popov (Проблемы особо опасных инфекций, 2012)
Protective antigen, extracted from Bacillus anthracis asporogenic recombinant strain, triggers progression of a high-grade adaptive immunity in vivo. Two-fold immunization of rabbits with the purified protein preparation in a dose of 50 mcg induces production of specific antibodies in titers higher than those registered in case of immunization with vaccine or genetically engineered anthrax strains. It is determined that the recombinant B. anthracis strain initiates further production of antibodies towards S-layer protein of anthrax agent.